2017
DOI: 10.1167/iovs.16-20785
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Pupillary Hippus in the Autonomic Nervous System

Abstract: Pupillary hippus can be extinguished by antagonizing the PNS, whereas agonizing the SNS dilates the pupil without affecting hippus. This suggests that hippus originates from central PNS activity, and not from SNS activity, or oscillations in the balance between PNS and SNS at the pupil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 38 publications
5
41
4
Order By: Relevance
“…This is in line with the idea that sleepiness induces slow rhythmic changes of pupil size that are also referred to as pupillary hippus or fatigue waves Loewenfeld, 1952, 1962;Hornung, 1968;Bouma and Baghuis, 1971). Recent research demonstrated that these pupillary oscillations are associated primarily by parasympathetic influence (Turnbull et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
“…This is in line with the idea that sleepiness induces slow rhythmic changes of pupil size that are also referred to as pupillary hippus or fatigue waves Loewenfeld, 1952, 1962;Hornung, 1968;Bouma and Baghuis, 1971). Recent research demonstrated that these pupillary oscillations are associated primarily by parasympathetic influence (Turnbull et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
“…The pupil can also undergo periods of spontaneous, oscillating constrictions, and dilations that occur independently of changes in illumination or of eye movements. These changes are termed pupillary “hippus” and are thought to result primarily from parasympathetic nervous system activity (Turnbull et al, 2017 ). Pupillary hippus is reduced in periods of wakefulness and, like dilation, may be a useful measurement of behavioral state (Lüdtke et al, 1998 ; Prasad et al, 2011 ).…”
Section: Mechanisms Controlling Pupil Diameter and The Effects Of Lummentioning
confidence: 99%
“…Activation of the parasympathetic nervous system (PNS) results in contraction of the circular muscles of the pupil causing miosis. Some authors have suggested that PH could stem from a continuous sympathetic-parasympathetic antagonism [2]. Nevertheless, Turnbull and colleagues [2] have recently proposed that PH originates from central PNS activity, and not from SNS activity, or oscillations in the input from the PNS and SNS.…”
Section: Clinical Casementioning
confidence: 99%
“…Some authors have suggested that PH could stem from a continuous sympathetic-parasympathetic antagonism [2]. Nevertheless, Turnbull and colleagues [2] have recently proposed that PH originates from central PNS activity, and not from SNS activity, or oscillations in the input from the PNS and SNS. They studied 36 normal subjects without central nervous system pathology.…”
Section: Clinical Casementioning
confidence: 99%
See 1 more Smart Citation